2022
DOI: 10.1021/acsomega.1c06880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Porosity on SARS-CoV-2 Fomite Infectivity

Abstract: Previous reports indicated the low stability of severe actute respiratory syndrome coronovirus 2 (SARS-CoV-2) on various porous surfaces, but the role of porosity was unclear because there was no direct comparison between porous and nonporous solids of the same chemistry. Through comparing pairs of solids with very similar chemistry, we find that porosity is important: porous glass has a much lower infectivity than nonporous glass. However, porosity is not sufficient to lower infectivity; permeability, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Lastly, we would like to highlight that the results of our present work, alongside a number of recent studies ,,, by Ducker and coworkers amid COVID-19, indicate explicitly that hydrophilic and porous surface coatings could be an effective strategy against the surface transmission of respiratory pathogens. Unlike antimicrobial surface coating approaches whereby nanoparticles are incorporated in a matrix, the cellulose thin film reported in this study provides a practical and sustainable antimicrobial solution.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Lastly, we would like to highlight that the results of our present work, alongside a number of recent studies ,,, by Ducker and coworkers amid COVID-19, indicate explicitly that hydrophilic and porous surface coatings could be an effective strategy against the surface transmission of respiratory pathogens. Unlike antimicrobial surface coating approaches whereby nanoparticles are incorporated in a matrix, the cellulose thin film reported in this study provides a practical and sustainable antimicrobial solution.…”
Section: Resultssupporting
confidence: 65%
“…The fundamental principle of a different strategy for virus inactivation is thus to target the respiratory droplets as opposed to the virions within. The porous nature of a surface coating can facilitate an imbibition process that is much faster than the diffusion-limited evaporation, which spreads and drains the virus-containing droplets quickly. The virus is subsequently dried within the porous matrix and loses infectivity by up to 100-fold during drying . With the virus being trapped and adhering to the pores below the top surface, microbial transfer through finger touching or rubbing can also be significantly reduced .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Chin et al (2020), who measured the half-life of SARS-CoV-2 on porous and non-porous materials, discovered that SARS-CoV-2 survived for approximately 3 h on porous materials such as thin paper and 7 day on non-porous materials such as plastics [ 9 ]. Hosseini et al (2022) compared the antiviral effects of the same materials with different porosities [ 128 ]. The results indicated that the effects are related to surface water absorption, drying time, or viruses being trapped in the structures [ 128 , 129 , 130 ].…”
Section: Microbicidal Surfacementioning
confidence: 99%
“…Hosseini et al (2022) compared the antiviral effects of the same materials with different porosities [ 128 ]. The results indicated that the effects are related to surface water absorption, drying time, or viruses being trapped in the structures [ 128 , 129 , 130 ]. In contrast to the pillar structure required for the mechano-bactericidal surface, a porous structural morphology may be an important basis in designing antiviral surfaces and should be further explored.…”
Section: Microbicidal Surfacementioning
confidence: 99%
“…Agreeing with this finding, Chatterjee et al established a relationship between the faster droplet evaporation in porous materials as the leading cause of the lower contamination risk, compared to nonporous solid surfaces. Similarly, Hosseini et al identified virus inactivation due to the fast droplet drying in porous materials, hypothesizing the cause to be the increased area of the air–water interface. Interestingly, the enhanced drying in porous materials due to the expansion of the wetted surface area under evaporation has been experimentally and theoretically verified by Gonçalves et al Once the primary role of the face mask is the protection of oneself and its surroundings, the understanding of the face mask’s surface wettability, the interaction with droplets containing pathogens, and its evaporation becomes of great interest.…”
Section: Introductionmentioning
confidence: 99%